Factores psicosociales que influyen en el tratamiento de diabetes mellitus tipo 2 Riobamba, 2019 - Castillo Orozco, Danny Javier (2020)
Diabetes mellitus is a significant initial disease in public health around the world and is one of the most frequent diseases due to the severity and variety of its chronic complications, it is identified by chronic hyperglycemia and by its improper metabolism of carbohydrates, the lipids, and proteins that are produced by insulin deficiency. The main objective of this research work is to publicize the psychosocial factors that influence the treatment of type 2 diabetes mellitus; the study was carried out in the outpatient area of Diabetology of the Riobamba Provincial General Teaching Hospital, information is obtained through of statistical data using Psychological tests to evaluate psychosocial factors. Besides, surveys were conducted to determine metabolic control and self-care measures, with a sample of 50 patients. Given that SI influences psychosocial factors since patients face this pathology in both a positive and negative way according to the help they receive from the social and family support network since it is essential for the patient to have true self-care of himself.